GamiTool: supporting instructors in the gamification of MOOCs - Ortega-Arranz, Alejandro; Asensio-Pérez, Juan I.; Martínez-Monés, Alejandra; Bote-Lorenzo, Miguel L.; Ortega-Arranz, Héctor; Kalz, Marco (IEEE access, 2022)
Reward-based gamification strategies are proposed as a promising technique to increase student engagement in Massive Open Online Courses (MOOCs), following its success in other small-scale educational settings. However, these strategies imply a number of orchestration tasks (e.g., design, management) that are usually carried out by instructors, and which may hinder their use and adoption. Furthermore, some MOOC distinctive features (e.g., scale, 24/7 availability, etc.) have considerable implications on how these gamification strategies are orchestrated, resulting in an unmanageable instructors’ workload in cases of manual operation. Therefore, an eventual adoption of gamification in MOOCs calls for automatic systems capable of decreasing the additional workload of instructors. The limitations identified in the current solutions (e.g., non-usable graphical interfaces, inflexible gamification designs) led us to propose and develop a new gamification system named GamiTool. An evaluation with 19 MOOC instructors and gamification designers showed the high design expressiveness, usability and potential for adoption of GamiTool. Hence, GamiTool can be used by instructors to improve students’ engagement, and also, by researchers to keep understanding the effects of gamification in MOOC settings.